2016
DOI: 10.3389/fphys.2016.00415
|View full text |Cite
|
Sign up to set email alerts
|

Why Is there a Limit to the Changes in Myofilament Ca2+-Sensitivity Associated with Myopathy Causing Mutations?

Abstract: Mutations in striated muscle contractile proteins have been found to be the cause of a number of inherited muscle diseases; in most cases the mechanism proposed for causing the disease is derangement of the thin filament-based Ca2+-regulatory system of the muscle. When considering the results of experiments reported over the last 15 years, one feature has been frequently noted, but rarely discussed: the magnitude of changes in myofilament Ca2+-sensitivity due to myopathy-causing mutations in skeletal or heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 73 publications
1
28
0
Order By: Relevance
“…Myofilament Ca 2+ sensitivity has been previously shown to be essential in the manifestation of DCM pathophysiology [3235]. To note, the TnT R141W mutation showed significantly Ca 2+ desensitization and also displayed an increase in Ca 2+ transient amplitudes as a consequence [12].…”
Section: Discussionmentioning
confidence: 99%
“…Myofilament Ca 2+ sensitivity has been previously shown to be essential in the manifestation of DCM pathophysiology [3235]. To note, the TnT R141W mutation showed significantly Ca 2+ desensitization and also displayed an increase in Ca 2+ transient amplitudes as a consequence [12].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of mutations in troponin subunits have been found to be associated with cardiomyopathies and have been extensively studied. Mutations in TNNNT2 and TNNI3 genes are significant causes of hypertrophic cardiomyopathy and dilated cardiomyopathy, whilst mutations in in TNNC1 are rare causes of these cardiomyopathies, Functionally the HCM mutations all seem to increase myofilament Ca 2+− sensitivity by about twofold (Marston 2011(Marston , 2016 and this is proposed to be disease-causing (Spudich 2014). In contrast, the effect of DCM mutations on Ca 2+ sensitivity is variable (Marston 2011;Memo et al 2013).…”
Section: Modulation Of the Ca 2+ Switch By Mutationsmentioning
confidence: 99%
“…It has been reported that HCM mutations in MYBPC3, MYH7 , and MYL2 cause enhanced myofibrillar Ca 2+ -sensitivity in muscle strips (see Marston, 2016). This was presumed to be due to allosteric interactions between the thick and thin filaments, however the results with the cat samples indicates that troponin is itself altered secondary to the HCM mutations in another gene.…”
Section: Discussionmentioning
confidence: 99%